Biooxidation of Iron by Acidithiobacillus ferrooxidans in the Presence of D-Galactose: Understanding Its Influence on the Production of EPS and Cell Tolerance to High Concentrations of Iron - Saavedra, Albert; Aguirre, Paulina; Gentina, Juan Carlos (Frontiers in Microbiology, 2020)
Acidithiobacillus ferrooxidans, together with other microorganisms, has an important role on bio-hydrometallurgical processes. Such bacterium gets its energy from the oxidation of ferrous ion and reduced sulfur; in the first case, the accumulation of ferric ion as a product can cause its inhibition. It is known that the extracellular polymeric substances (EPS) may have an important role in the adaptation and tolerance to diverse inhibiting conditions. In the present study, it was tested how D-galactose can influence the production of extracellular polymeric substances (EPS) on At. ferrooxidans by evaluating at the same time its biooxidant activity and capacity to tolerate high concentrations of ferric ion. The visualization and quantification of EPS was done through a confocal laser scanning microscope (CLSM). The results show that at low cellular concentrations, the D-galactose inhibits the microbial growth and the biooxidation of ferrous ion; however, when the quantity of microorganisms is high enough, the inhibition is not present. By means of chemostat tests, several concentrations of D-galactose (0; 0.15; 0.25 and 0.35%) were evaluated, thus reaching the highest production of EPS when using 0.35% of this sugar. In cultures with such concentration of D-galactose, the tolerance of the bacterium was tested at high concentrations of ferric ion and it was compared with cultures in which sugar was not added. The results show that cultures with D-galactose reached a higher tolerance to ferric ion (48.15 ± 1.9 g L-1) compare to cultures without adding D-galactose (38.7 ± 0.47 g L-1 ferric ion). Also it was observed a higher amount of EPS on cells growing in the presence of D-galactose suggesting its influence on the greater tolerance of At. ferrooxidans to ferric ion. Therefore, according to the results, the bases of a strategy are considered to overproduce EPS by means of At. ferrooxidans in planktonic state, so that, it can be used as a pre-treatment to increase its resistance and tolerance to high concentrations of ferric ion and improve the efficiency of At. ferrooxidans when acting in biohydrometallurgical processes.